Pengaruh Konsentrasi Kepemilikan, Struktur Dewan Komisaris, dan Leverage Terhadap Risk Management Disclosure - Syafira Ramadhea Jr; Dita Maretha Rissi; Ria Angriani; Dissa Elvaretta; Nurul Hafizah (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2023)
This study was conducted with the aim of collecting empirical evidence regarding the impact of (1) the level of concentration of share ownership on risk management disclosure, (2) the role of the board of commissioners structure in risk management disclosure, and (3) the level of leverage on risk management disclosure. The subjects of this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2020-2022 period. This research is quantitative and includes a population of 191 manufacturing companies listed on the IDX during the period. The research sample consists of 40 manufacturing companies selected by purposive sampling method. The data used in this study are secondary data derived from financial reports and annual reports of manufacturing companies. To test the hypothesis in this study, the multiple linear analysis method was used with independent variables including concentration of share ownership, the role of the board of commissioners, and the level of leverage, while the dependent variable was the level of risk management disclosure. The data was processed using SPSS for Windows software. The results showed that the role of the board of commissioners structure has a significant influence on risk management disclosure, while the concentration of share ownership and the level of leverage do not have a significant impact on risk management disclosure.